Far From The Madding Crowd - Hardy T. (London Book Club Associaties John Player and Sons, 1975)
The title of this novel is somewhat ironic as the "madding crowd" does enter and violently isrupt the life of Bathsheba Everdene, the beautiful and independent young heiress. Sergeant Troy, the fascinating but faithless soldier, and Mr. Boldwood, the lonely bachelor of repressed but violent passions, both court her, deflecting her life from its intended course of rustic happiness with the tenderest of her suitors, Gabriel Oak, and bringing violence and scandal into the idyllic rural community of which she is mistress. In his account of the love of these three men and their influence on Bathsheba, Hardy shows a deep understanding of human emotion and this one of the greatest of his love stories. But at the same time the action is influenced and dominated by the age-old activities of rural life.
Keywords: 82-3 (NhUDOVNQ PROZAs